2016
DOI: 10.1002/pmic.201600290
|View full text |Cite
|
Sign up to set email alerts
|

An enlarged cell wall proteome of Arabidopsis thaliana rosettes

Abstract: Plant cells are surrounded by cell walls playing many roles during development and in response to environmental constraints. Cell walls are mainly composed of polysaccharides (cellulose, hemicelluloses and pectins), but they also contain proteins which are critical players in cell wall remodeling processes. Today, the cell wall proteome of Arabidopsis thaliana, a major dicot model plant, comprises more than 700 proteins predicted to be secreted (cell wall proteins-CWPs) identified in different organs or in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…Gilbert and Schulze (2019) identified ArathEULS3 peptides in Arabidopsis root membranes [49]. Additionally, peptides derived from ArathEULS3 were found in the cell wall proteome of A. thaliana rosettes and mature stems [50,51]. Moreover, the experiment investigating the cell wall proteome of two Arabidopsis ecotypes Columbia (Col) and Shahdara (Sha) grown at 22 • C and at 15 • C, respectively, revealed an increase in ArathEULS3 peptides in both ecotypes at a lower temperature [52].…”
Section: Discussionmentioning
confidence: 98%
“…Gilbert and Schulze (2019) identified ArathEULS3 peptides in Arabidopsis root membranes [49]. Additionally, peptides derived from ArathEULS3 were found in the cell wall proteome of A. thaliana rosettes and mature stems [50,51]. Moreover, the experiment investigating the cell wall proteome of two Arabidopsis ecotypes Columbia (Col) and Shahdara (Sha) grown at 22 • C and at 15 • C, respectively, revealed an increase in ArathEULS3 peptides in both ecotypes at a lower temperature [52].…”
Section: Discussionmentioning
confidence: 98%
“…The proportions of proteins that we identified with signal peptides, membrane anchors, or transmembrane domains are comparable with similar proteomic studies ( Supplemental Table S4). Hervé et al (2016) recently identified 1,093 proteins from the cell walls of Arabidopsis leaves; of these, they classified 361 (33%) proteins as cell wall localized on the basis of possessing a signal peptide or a transmembrane domain and lacking retention signals. Of the cell wall proteome of Hervé et al (2016), 72 proteins are in common with our data set.…”
Section: Comparison With Similar Proteomic Studiesmentioning
confidence: 99%
“…Hervé et al (2016) recently identified 1,093 proteins from the cell walls of Arabidopsis leaves; of these, they classified 361 (33%) proteins as cell wall localized on the basis of possessing a signal peptide or a transmembrane domain and lacking retention signals. Of the cell wall proteome of Hervé et al (2016), 72 proteins are in common with our data set. Rutter and Innes (2017) isolated extracellular vesicles from Arabidopsis leaves and identified 598 proteins in total, 204 (34%) of which they classified as extracellular.…”
Section: Comparison With Similar Proteomic Studiesmentioning
confidence: 99%
“…With this new cell wall proteomics study, the total number of A. thaliana CWPs identified is of 805, that is between two fifths and one half of the expected total number of CWPs . The cell wall proteomics atlas of A. thaliana thus remains the best described, including large proteomes for all vegetative organs (roots, rosettes and stems) as well as etiolated hypocotyls and cell suspension cultures . This description should now be completed by the analysis of different stages of development of each organ and of post‐translational modifications.…”
mentioning
confidence: 99%